A prospective, parallel group, open label, observational study to compare efficacy and feto-maternal outcomes in treatment of pregnancy induced hypertensive patients - Afreen, Shaistha; A., Rishtha; P., Swathi; Nasreen, Atiya Tara; Goud, Surya Aditya; Tabassum, Khaleequa; Nadeem, Md. Tarique (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Pregnancy induced hypertension (PIH) is defined as elevation in blood pressure 140/90 mmHg or greater after 20 weeks of gestation on two occasions more than 4 hours apart in a newly diagnosed patients. Complications of pregnancy are the major health problems leading to maternal and perinatal mortality and morbidity. Some anti-hypertensive drugs are commonly used to control hypertension. Methods: A prospective, parallel group, open label observation study was carried out at SVS Medical Hospital, Mahabubnagar. Patients were divided into three groups based on severity of hypertension and the drug used for treatment. Results: Of 120 patients diagnosed with PIH majority (50%) of women were in the age group of 21-24 years with 33-37 gestational age. In the present study there was a significant reduction in BP after the treatment with Labetalol when compare to Nifedepine and Methyldopa. Although, all the three groups have shown significant reduction in BP during 24 hrs treatments and the mean time to achieve target BP was shown less in Labetalol group when compare to Methyldopa and Nifedepine and the maximum doses required to achieve target BP was in between 4-6 doses/day. 40% of complication observed was HELLP syndrome. Conclusions: Our study coincides with the previous findings that labetolol is an efficacious and safer drug for use in control of PIH and mean time required to achieve target BP is low when compared to nifedipne and methyldopa.